Prevalence of Rotavirus, Adenovirus, and Astrovirus Infections among Patients with Acute Gastroenteritis in, Northern Iran - R Hamkar; Y Yahyapour; M Noroozi; K Nourijelyani; S Jalilvand; L Adibi; S Vaziri; AA Poor-Babaei; A Pakfetrat; A Pakfetrat; R Savad-Koohi (Tehran University of Medical Sciences, 2010)
Background: The aim of the study was to determine the incidence of non-bacterial acute gastroenteritis associated with diarrheal diseases in Mazandaran Province, northern Iran. Methods: A total of 400 symptomatic cases from patients with acute gastroenteritis from Mazandaran Province in Iran were screened using EIA method for the presence of rotavirus, adenovirus and astrovirus during 2005-2006. Chi-square tests were used for testing relationships between different variables. Results: Rotavirus, adenovirus and astrovirus were detected in 62%, 2.3%, and 3% of samples, respectively. The maximum rate of rotaviruses was detected in the <1-year-old age group, while minimum rate was found in the 10 years and older age group. Astrovirus and adenovirus were detected predominantly in the 2-5-year-old age group of children, with a prevalence of 8.3% and 3.5% respectively. All studied viral gastroenteritis peaked in the winter, and minimum rate were found in summer. Conclusion: Our statistical analyzes indicated that viral gastroenteritis, especially Rota-viral, had the highest number of occurrences in colder seasons notably in winter and more frequently were observed among younger children.